EFFECT OF MALE GONADAL HORMONES ON CHANGES IN THE CARDIOVASCULAR SYSTEM CAUSED BY ACUTE COLD INJURY - Taran, I.V.; Voloshchuk, N.I.; Hodovan, N.L.; Maschevska, O.V.; Lozinska, M.S.; Ivanitsa, A.O.; Hruzd, V.V. (World of Medicine and Biology, 2024)
Gender differences in the functioning of the human body are considered the basis of the development of gender pharmacology. The peculiarities of the structure of the male and female bodies produce a wide range of physiological and psychological reactions that ensure each species' biological role. It is known that in extreme conditions, which include low temperatures, the mental and physical reactions of individuals of different sexes differ. The main target organs of cold injury are the central nervous and cardiovascular systems. The state of the cardiovascular system depends on many factors, one of which is the level of sex hormones. It is known that men tolerate low temperatures worse, and the survival rate of rats under conditions of acute general cooling increases when the testosterone level decreases. However, information on changes in the cardiovascular system's work under different levels of body saturation with testosterone is unclear and needs clarification. The studies show changes in the electrocardiograms of rats, changes in the hormonal background of males, and changes in heart rate, R and S wave amplitudes, and QT and ST intervals. When an acute cold injury was simulated, the electrocardiogram changes became more extensive: the R amplitude statistically decreased, and the S amplitude increased. In addition, the PQ, RS, QT, and ST intervals were statistically lengthened. The performed gonadectomy reduced the expressiveness of the changes on the electrocardiogram and restored some parameters to those considered within the limits of statistical error. Thus, the expressiveness of changes in the electrocardiogram under the influence of cold in males with a normal testosterone level was significantly greater than in animals after castration. A similar trend was observed in the analysis of blood pressure changes in male rats with different hormonal backgrounds.
Keywords: gender; cold injury; ECG; blood pressure; testosterone; rats; experiment